2015
DOI: 10.1128/jvi.01842-15
|View full text |Cite
|
Sign up to set email alerts
|

R5 Macrophage-Tropic HIV-1 in the Male Genital Tract

Abstract: The entry tropism of HIV-1 Env proteins from virus isolated from the blood and genital tract of five men with compartmentalized lineages was determined. The Env proteins isolated from the genital tract of subject C018 were macrophage-tropic proteins, while the remaining cloned env genes encoded R5 T cell-tropic proteins. The detection of a macrophage-tropic lineage of HIV-1 within the male genital tract strongly suggests that evolution of macrophage-tropic viruses can occur in anatomically isolated sites outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…we were able to sample virus before and shortly after the person started therapy and found that both the standard CD4‐high (T cell‐tropic) and the unexpected CD4‐low (M‐tropic) viruses were reduced equivalently in blood viral load by therapy, indicating both were replicating in short‐lived T cells (Joseph and Swanstrom, unpublished data). Similarly, we have detected M‐tropic virus in the semen of one male . We hypothesize that in each of these cases the M‐tropic virus evolved in an isolated tissue depleted of CD4+ T cells and was introduced into the systemic pool of replicating virus in the former or into draining seminal fluid in the latter.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…we were able to sample virus before and shortly after the person started therapy and found that both the standard CD4‐high (T cell‐tropic) and the unexpected CD4‐low (M‐tropic) viruses were reduced equivalently in blood viral load by therapy, indicating both were replicating in short‐lived T cells (Joseph and Swanstrom, unpublished data). Similarly, we have detected M‐tropic virus in the semen of one male . We hypothesize that in each of these cases the M‐tropic virus evolved in an isolated tissue depleted of CD4+ T cells and was introduced into the systemic pool of replicating virus in the former or into draining seminal fluid in the latter.…”
Section: Introductionmentioning
confidence: 63%
“…Similarly, we have detected M-tropic virus in the semen of one male. 61 We hypothesize that in each of these cases the M-tropic virus evolved in an isolated tissue depleted of CD4+ T cells and was introduced into the systemic pool of replicating virus in the former or into draining seminal fluid in the latter.…”
Section: F I G U R E 1 M-tropic Hiv-1 Is Efficient At Entering Cells mentioning
confidence: 99%
“…Unlike CD4 + T cells, macrophages have low levels of surface CD4 and have mostly been observed in the central nervous system of infected patients [184, 185], late in disease [186] and more recently in the male genital compartment [187]. Probably the most well studied compartment as far as macrophage tropism is the central nervous system which has 4 types of macrophages; microglia, meningeal macrophages, perivascular macrophages and macrophages of the choroid-plexus [188].…”
Section: Traits Reported To Be Different Between Transmitted/founder mentioning
confidence: 99%
“…However, viruses that have been replicating independently in anatomically distinct regions such as the central nervous system where CD4+ T cells are less abundant, can evolve the ability to enter cells expressing lower densities of CD4, such as macrophages. This has been observed for compartmentalized lineages derived from both the CNS (27) and, in one case, the male genital tract (28). In order to determine whether compartmentalized, semen-derived lineages from our cohort have the ability to enter cells expressing a low density of CD4, we performed SGA of full-length HIV-1 env genes using viral RNA as the template for cDNA synthesis followed by PCR done at template end-point dilution.…”
Section: Resultsmentioning
confidence: 72%
“…Our observation that inflammation does not alter the frequency with which we detect semen-specific HIV-1 lineages suggests that, when compartmentalized lineages are present, they are most likely produced by cells in anatomical areas that are not in direct contact with the periphery. In one extreme case of this type of isolation we previously observed the presence of a macrophage-tropic variant in semen (28) which suggests that in this case there was sufficient depletion of CD4+ T cells, without replenishment, that the virus evolved to expand its target cell specificity. In the current study all of the viruses tested were T cell-tropic, requiring a high density of CD4 for efficient entry into cells.…”
Section: Discussionmentioning
confidence: 89%